IEEE/ACM International Conference on Computer Aided Design. ICCAD - 2000. IEEE/ACM Digest of Technical Papers (Cat. No.00CH3714
DOI: 10.1109/iccad.2000.896524
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of operation-centric hardware descriptions

Abstract: Most hardware description frameworks, whether schematic or textual, use cooperating finite state machines (CFSM) as the underlying abstraction. In the CFSM framework, a designer explicitly manages the concurrency by scheduling the exact cycle-by-cycle interactions between multiple concurrent state machines. Design mistakes are common in coordinating interactions between two state machines because transitions in different state machines are not semantically coupled. It is also difficult to modify one state mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 18 publications
0
36
0
1
Order By: Relevance
“…Like FLaSH, resource sharing is a focus of Bluespec [14], a hardware description language with a strong functional influence (e.g., higher-order functions, polymorphism). Bluespec's most distinctive feature is its use of "rules"-guarded atomic actions that are scheduled by a synthesized rule scheduler.…”
Section: Functional Descriptions To Hardwarementioning
confidence: 99%
“…Like FLaSH, resource sharing is a focus of Bluespec [14], a hardware description language with a strong functional influence (e.g., higher-order functions, polymorphism). Bluespec's most distinctive feature is its use of "rules"-guarded atomic actions that are scheduled by a synthesized rule scheduler.…”
Section: Functional Descriptions To Hardwarementioning
confidence: 99%
“…We choose an experimental operation-centric language [10] over mainstream RTL-based languages (e.g. RTL subset of Verilog or VHDL) to deal with the complexity of microprocessor designs.…”
Section: High-level Description and Synthesismentioning
confidence: 99%
“…Bluespec has been used at Sandburst, MIT and CMU to describe complex hardware, Previous work has also shown that small but complex designs described using TRS, the formalism underlying Bluespec, are amenable to formal verification [I], It has also been shown that a simple 5-stage MIPS pipeline can be synthesized from TRS's quite effciently [7,8] , What remains to be seen is if the correctnesscentric Bluespec design approach is able to generate RTL that is comparable to handwritten Verilog.…”
Section: Introductionmentioning
confidence: 99%